2012
DOI: 10.3892/mmr.2015.3520
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier permeability of Gualou Guizhi granules and neuroprotective effects in ischemia/reperfusion injury

Abstract: The present study aimed to estimate the blood-brain barrier (BBB) permeability of Gualou Guizhi granules (GLGZG) in normal rats and in rat models of ischemia/reperfusion (I/R) injury, and to examine the neuroprotective effects of GLGZG. A sensitive high‑performance liquid chromatography-quadrupole-time of flight-mass spectrometry analytical method was developed to determinate the components of GLGZG in the plasma and brain tissue. Middle cerebral artery occlusion (MCAO) in rats served as a model of in vivo I/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Moreover, our recent study suggested that PF exerted stable and potent neuroprotective effects against cerebral ischemic injury and protected against N-methyl-D-aspartate (NMDA)-induced cell apoptosis and neuronal loss (22). In a previous study of ours, we also found that PF was one of the compounds found in the brain tissue and cerebrospinal fluid of rats administerd PF after suffering cerebral ischemia injury (28). Thus, as a continuation, the aim of this study was to further investigate the neuroprotective effects of PF against glutamate-induced PC12 cellular cytotoxicity and to elucidate whether the mitochondrial apoptosis-associated pathway is involved in these neuroprotective effects.…”
Section: Introductionsupporting
confidence: 51%
“…Moreover, our recent study suggested that PF exerted stable and potent neuroprotective effects against cerebral ischemic injury and protected against N-methyl-D-aspartate (NMDA)-induced cell apoptosis and neuronal loss (22). In a previous study of ours, we also found that PF was one of the compounds found in the brain tissue and cerebrospinal fluid of rats administerd PF after suffering cerebral ischemia injury (28). Thus, as a continuation, the aim of this study was to further investigate the neuroprotective effects of PF against glutamate-induced PC12 cellular cytotoxicity and to elucidate whether the mitochondrial apoptosis-associated pathway is involved in these neuroprotective effects.…”
Section: Introductionsupporting
confidence: 51%
“…Stroke, with predominant clinical manifestations of ischemia of the brain and hemorrhagic injury, is a major cause of mortality worldwide ( Li et al, 2015 ). The blood-brain barrier (BBB) is a diffusion barrier that selectively blocks influx and efflux of most compounds between blood and brain ( Ballabh et al, 2004 ).…”
Section: Pharmacological Activities Against Nddsmentioning
confidence: 99%
“…Importantly, some compounds have been demonstrated to pass the blood-brain barrier and to reach the brain tissue ( e.g . albiflorin, paeoniflorin and liquiritin), which may further explain the effect of FAEW on the central nervous system 33 .…”
Section: Discussionmentioning
confidence: 92%